2017
DOI: 10.1002/aenm.201602579
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Monolithic Co3Se4 Nanowire Electrodes for Oxygen Evolution and Overall Water Splitting with High Efficiency and Extraordinary Catalytic Stability

Abstract: using electrocatalysts, the OER will take place at a high overpotential leading to significant losses of the overall efficiency of water splitting. Although RuO 2 and IrO 2 are highly efficient catalysts for the OER, [1b] the exorbitant price and scarcity of Ru and Ir severely restrict their widespread use in electrolyzers.Remarkable progress has been made in developing efficient nonprecious OER electrocatalysts, such as perovskite oxides, [3] transition metal (TM) oxides, [4] (oxy)hydroxides, [5] phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
181
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(186 citation statements)
references
References 58 publications
5
181
0
Order By: Relevance
“…[1][2][3][4] However, the development of practical full water splitting (FWS) applications encountered very serious challenges: the sluggish kinetics of OER and HER. [21,22] Inspired by above considerations, we here report the fabrication of Fe-doped Co carbonate hydroxide nanosheets array on 3D conductive Ni foam (FCCH/NF) as a monolithic OER-HER bifunctional electrocatalyst for FWS. Additionally, the direct growth of catalyst grown on 3D conductive substrates has been considered to be an effective way for exposing more active sites, facilitating mass transport, and thus leading to more efficient use of active sites and increasing the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, the development of practical full water splitting (FWS) applications encountered very serious challenges: the sluggish kinetics of OER and HER. [21,22] Inspired by above considerations, we here report the fabrication of Fe-doped Co carbonate hydroxide nanosheets array on 3D conductive Ni foam (FCCH/NF) as a monolithic OER-HER bifunctional electrocatalyst for FWS. Additionally, the direct growth of catalyst grown on 3D conductive substrates has been considered to be an effective way for exposing more active sites, facilitating mass transport, and thus leading to more efficient use of active sites and increasing the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…For electrocatalysis, “d” electrons present in transition metals participate in bonding with adsorbates; thus the introduction of low electronegativity “Se” into the Zn 1‐ x Fe x –LDH can effectively modify the “d” orbital electronic structure and enhances the electrocatalytic activities . Besides, in order to find the electrochemical active surface area (ECSA) of Zn 1‐ x Fe x –LDH and Zn 1‐ x Fe x –oxyselenide, the previously established ECSA = C dl / C s equation was used, where C dl is electrochemical double‐layer capacitance and C s is specific capacitance of a flat smooth surface of the electrode material, which is presumed to be 40 mF cm −2 according to previous reports . Non‐Faradaic region (1.02–1.22 V vs RHE) cyclic voltammograms (Figure S3a,b, Supporting Information) at scan rates of 50–150 mV s −1 were used for C dl calculation, which was estimated by plotting the difference of the anodic and cathodic current densities (Δ j = j a − j c ) at 1.1 V versus scan rate (Figure S3c,d, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…During OER and HER stability studies, the electrode materials are expected to undergo structural/morphological changes and then affect the electrocatalytic performance. Very recent studies have demonstrated that under OER operational conditions non‐oxide‐based transition metal (TM) catalysts undergoes an in situ electrochemical transformation and form TM‐based hydroxide/(oxy)hydroxide, which is found to be the true catalytically active species for the OER. Moreover, it has been shown that in most cases the in situ transformed TM hydroxide/(oxy) hydroxide exhibits better OER performance than the pristine TM hydroxide/(oxy)hydroxide obtained by direct synthesis .…”
Section: Resultsmentioning
confidence: 99%
“…[36] In integrated electrode, rational design of catalysts and current collector should be seriously addressed, including increasing effective active sites of the catalyst and promoting electron transport from active catalyst to external circuit via current collector. [38,39] Meanwhile, the core/shell nanowire array structure is beneficial to promote gas release and electrolyte permeation, and realize full contact between electrolyte and catalyst. 3D hierarchical architecture with core/shell nanowire array surface morphology is a kind of high aspect ratio structure, and can significantly accelerate electron transport and increase effective catalytic active sites of catalyst.…”
Section: Introductionmentioning
confidence: 99%